Intriguing Carbon Flake Formation during Microwave‐Assisted Hydrothermal Carbonization of Sodium Lignosulfonate. Issue 8 (20th February 2020) - Melilli, Giuseppe; Adolfsson, Karin H.; Impagnatiello, Andrea; Rizza, Giancarlo; Hakkarainen, Minna
Abstract: Elongated carbon structures, here denoted as carbon flakes (CF), are revealed after microwave‐assisted hydrothermal carbonization of sodium lignosulfonate. The morphology of formed CF is investigated by transmission electron microscopy and atomic force microscopy. Interestingly, a wide range of length distributions (between 100 and 700 nm) and a relatively constant aspect ratio and thickness are observed, indicating structures clearly different from the carbon spheres commonly formed during hydrothermal carbonization of lignocellulosic biomass. Moreover, X‐ray diffraction, Raman spectroscopy, Fourier transform infrared spectroscopy, and X‐ray photoelectron spectroscopy provide further information of the chemical structure, which consist mainly of nanographitic domains with a high degree of defects such as oxygenated functional groups, hybridized sp 3 carbon, and aliphatic side chains. Furthermore, new insights into the formation mechanisms are uncovered and the formation is speculated to proceed through the combined effect of microwave irradiation and a heterogeneous solid–solid conversion. The formed CF are anticipated as highly interesting products for a variety of material applications. Abstract : Formation of elongated carbon flakes is revealed after microwave‐assisted hydrothermal carbonization of sodium lignosulfonate. The formed carbon flakes are shown to consist mainly of nanographitic domains with a high degree of defects such as oxygenated functional groups. Furthermore, new insights into the formation mechanisms are uncovered. Carbon flakes are anticipated as highly interesting products for variety of material applications.